Professional issues in IT - Bott, Frank; Taylor, Neil (BCS, The Chartered Institute for IT, 2022)
Relevant to all sizes of organisation, this book addresses the social, legal, financial, organisational and ethical issues faced by IT professionals, in alignment with the BCS HEQ 'Diploma in IT' core module: Professional Issues in Information Systems Practice. This new edition takes into account the social and legal implications of the changes to legislation and technology over recent years, including the GDPR and Data Protection Act, health and safety, and the impact of IT on the environment.